Software Toolkits: Practical Aspects of the Internet of Things—A Survey - Feng Wang; Liang Hu; Jin Zhou; Yang Wu; Jiejun Hu; Kuo Zhao (International Journal of Distributed Sensor Networks)
The Internet of Things (IoT) is neither science fiction nor industry hype; rather it is based on solid technological advances and visions of network ubiquity that are zealously being realized. The paper serves to provide guidance regarding the practical aspects of the IoT. Such guidance is largely missing in the current literature in which the focus has been more on research problems and less on issues describing how to set up an IoT system and what software toolkits are required. This paper aims to bridge this gap by providing guidance in terms of the software toolkits that can be utilized by IoT practitioners and research students to set up a practical IoT system. The IoT is the combination of multiple techniques; a onefold technology cannot become the IoT. This is conducted in a multilayer approach that covers node and operating systems, middleware, databases, IoT energy harvesting method, and so forth. We hope that this survey serves to be useful to researchers and practitioners in practical aspects of IoT.